2018
DOI: 10.1007/s13659-018-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

Meroterpenoids from Ganoderma Species: A Review of Last Five Years

Abstract: Meroterpenoids are hybrid natural products that partially originate from the terpenoid pathway. Ganoderma meroterpenoids (GMs) are a type of meroterpenoids containing a 1,2,4-trisubstituted phenyl and a polyunsaturated terpenoid part. Over last 5 years, great efforts have been made to conduct phytochemistry research on the genus Ganoderma, which have led to the isolation and identification of a number of GMs. These newly reported GMs showed diverse structures and a wide range of biological activities. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…In this study, Ganoderma (Lingzhi) was chosen because it has been used extensively in Asian countries for more than 2,000 years, due to its various pharmacological effects, including immunomodulation, antibacterial, anticancer, antioxidant, and antiviral activities (Gao et al, 2003;Sliva, 2004;Yuen and Gohel, 2005;Joo et al, 2008;Sanodiya et al, 2009;Ma et al, 2011;Xu et al, 2011). Ganoderma is rich in active compounds, including triterpenoids, fatty acids, polysaccharides, peptides, and other chemicals (Sanodiya et al, 2009;Peng and Qiu, 2018), and that has led to the possibility of identifying FPR agonists and antagnosits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Ganoderma (Lingzhi) was chosen because it has been used extensively in Asian countries for more than 2,000 years, due to its various pharmacological effects, including immunomodulation, antibacterial, anticancer, antioxidant, and antiviral activities (Gao et al, 2003;Sliva, 2004;Yuen and Gohel, 2005;Joo et al, 2008;Sanodiya et al, 2009;Ma et al, 2011;Xu et al, 2011). Ganoderma is rich in active compounds, including triterpenoids, fatty acids, polysaccharides, peptides, and other chemicals (Sanodiya et al, 2009;Peng and Qiu, 2018), and that has led to the possibility of identifying FPR agonists and antagnosits.…”
Section: Introductionmentioning
confidence: 99%
“…Among these triterpenoids and meroterpenoids, C18 was identified to have strong inhibitory activities. C18 and 5 other structurally similar compounds (Figure 1), all Ganoderma meroterpenoids (GMs) (Peng and Qiu, 2018), were selected for further studies. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Notably, Ganoderma meroterpenoids have widely attracted attention in the past six years due to their intriguing structures and diverse biological activities. 8 All these efforts have illuminated and enriched the chemical prole of Ganoderma secondary metabolites, which has made it possible for Ganoderma to be developed as a regular drug rather than as a dietary supplement. 9,10 Sesquiterpenoids are the most abundant type of secondary metabolites in mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Y. M. Yan et al reported six meroterpenoids with neural stem cells proliferation-promoting activity from this fungus. 18 In order to explore diverse constituents for the identication of bioactive natural products from Ganoderma, a detailed chemical investigation on G. lingzhi led to the isolation of six rarely-encountered gymnomitrane-type sesquiterpenoids (1)(2)(3)(4)(5)(6), an unusual type sesquiterpene (8), a polyketide (7) and an unusual ergosterol (9) from the low-polarity fractions of the crude extract ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%